Biogeochemical evidence raises questions on the longevity of warming‐induced growth enhancements in wet boreal forests - Susan E. Ziegler; Sharon A. Billings; Frances A. Podrebarac; Kate A. Edwards; Andrea Skinner; Kate M. Buckeridge; Trevor C. VandenBoer (Ecosphere)
Abstract In wet regions, temperature increases can prompt increases in vegetation growth. Vegetation responses are determined in part by N and P availability, yet the relative importance of N‐ versus P‐cycling supporting growth is unclear. Prompted by studies demonstrating that warming‐enhanced N cycling supports greater productivity and soil C stocks in warmer forests along a wet boreal forest transect, we tested the hypothesis that enhanced organic matter cycling supports greater P demand in relatively warm forests. We further asked whether evidence from soil and litterfall fluxes indicates increases in P demand are met in these forests or potentially pose a limit on warming‐enhanced productivity. Elevated tree growth and litterfall rates coupled with similar litterfall P concentrations suggest P demand is greater at warmer sites. By assessing multiple soil N and P stocks, inputs, and stoichiometry, we observed three lines of evidence indicating that this greater P demand is met through a combination of plant tissue plasticity and adequate surface soil P supplies. First, warming‐enhanced N‐cycling results in an increase in N:P of surface soils and litterfall inputs indicating a reduction in needle litter P relative to N. Second, organic layer C:P and P stocks were maintained across latitude despite increases in litterfall P inputs in the warmest forests suggesting increased cycling and retention of P by trees. Third, in contrast with soil N, estimates of soil P residence times are not coupled with those of C, and soil C:P does not correlate with tree growth across sites signifying that N, not P, may limit tree growth in these forests. Results here provide evidence that increased productivity with warming and enhanced N cycling in wet boreal forests is not likely to be limited by available P over the decadal timescale represented by the temperature gradient along this climate transect. However, similarities observed between warming‐enhanced N availability in the current study's forests and that in boreal forests receiving high N additions indicate a need to better understand how boreal trees may adapt to shifts away from N limitation. Such new knowledge is needed to improve our understanding of the longevity of this important climate feedback.